Succeeding with adult ADHD : daily strategies to help you achieve your goals and manage your life - Levrini, Abigail (APA LifeTools, 2023)
"This expanded and updated new edition of psychologist Abigail Levrini's bestselling book offers realistic, proven strategies to help adults with ADHD lead more fulfilling and productive lives"--